Muslim Stereotypes, the “Other”, and the Consequences in Kamila Shamsie’s Home Fire - Akbar, Jawad; Mira Utami (Muslim English Literature, 2025)
This study examines the stereotypical portrayal of Muslims in Kamila Shamsie’s Home Fire as the “Other” within an Orientalist framework. Stereotyping is understood as a prejudiced, exaggerated, and often inaccurate set of beliefs attached to particular groups, while Orientalism refers to the Western tradition of depicting the East as inferior, backward, and threatening. The novel reflects these intersecting paradigms through its representation of Muslim characters particularly the Adil Pasha’s family, and, more specifically the treatment on Parvaiz Pasha after his involvement with a militant organization. Despite his British citizenship, Parvaiz is denied burial in Britain, symbolizing his repositioning from citizen to outsider. The textual analysis undertaken in this study, grounded in Allport’s (1954) theory of stereotyping and Said’s (1978) theory of Orientalism, reveals how Muslims are framed as inherently suspect, dangerous, or undeserving of equal rights. The research demonstrates that Shamsie’s narrative exposes deeply embedded Western biases that continue to shape the experiences of Muslim communities in diasporic contexts. Ultimately, the study highlights how the novel challenges the dominant Orientalist discourse by foregrounding the human consequences of stereotyping, marginalization, and exclusion.